Purinergic Ligands as Potential Therapeutic Tools for the Treatment of Inflammation-Related Intestinal Diseases - Dal Ben, Diego; Antonioli, Luca; Lambertucci, Catia; Fornai, Matteo; Blandizzi, Corrado; Volpini, Rosaria (Frontiers in Pharmacology, 2018)
Inflammation-related intestinal diseases are a set of various conditions presenting an overactive enteric immune system. A continuous overproduction of pro-inflammatory cytokines and a decreased production of anti-inflammatory modulators are generally observed, while morpho-functional alterations of the enteric nervous system lead to intestinal secretory and motor dysfunctions. The factors at the basis of these conditions are still to be totally identified and current therapeutic strategies are aimed only at achieving and maintaining remission states, by using therapeutic tools like aminosalicylates, corticosteroids, immunomodulators, biological drugs (i.e. monoclonal antibodies), and eventually surgery. Recent reports described a key role of purinergic mediators (i.e. adenosine and its nucleotides ATP and ADP) in the regulation of the activity of immune cells and enteric nervous system, showing also that alterations of the purinergic signaling are linked to pathological conditions of the intestinal tract. These data prompted to a series of investigations to test the therapeutic potential for inflammation-related intestinal conditions of compounds able to restore or modulate an altered purinergic signaling within the gut. This review provides an overview on these investigations, describing the results of preclinical and/or clinical evaluation of compounds able to stimulate or inhibit specific P2 (i.e. P2X7) or P1 (i.e. A2A or A3) receptor signaling and to modify the adenosine levels through the modulation of enzymes activity (i.e. Adenosine Deaminase) or nucleoside transporters. Recent developments in the field are also reported and the most promising purine-based therapeutic strategies for the treatment of inflammation-related gastrointestinal disorders are schematically summarized.